When is a male too hot? Fitness outcomes when mating with high temperature, sick males. (April 2022) - Castillo-Pérez, E. Ulises; Cargnelutti, Franco; Reyes-Ramírez, Alicia; Rocha-Ortega, Maya; Córdoba-Aguilar, Alex
Abstract: Infection may cause some insects to increase their body temperature to deal against pathogens successfully. However, one unclear aspect is whether females may use male temperature to discriminate sick from healthy partners. We tested this by using Tenebrio molitor beetles whose females use the intensity of male antennal and leg stroking that take place during mating, to discriminate among partners. We predicted that females will not choose males that are too hot and/or will penalize these male partners in terms of a reduced egg number and hatching success. We manipulated males by infecting them with an entomopathogenic fungus, and exposed these males versus control males to females. Infected and non-infected males increased their temperature during copulation but females did not choose on the basis of male's temperature or infection status. However, females laid fewer eggs and/or had a reduced hatching success after mating with infected males that had a body temperature higher than ca. 24 °C. We postulate that male temperature is another source of information involved in postcopulatory mate choice that, along with courtship traits, compose a multimodal signaling system. Graphical abstract: Image 1 Highlights: Females may assess male temperature during mating to avoid infected males. Sick males with temperature higher than 24 °C, ended up fathering fewer eggs. Females may penalize too hot, sick males in terms of reduced fitness.